Uji Kelayakan Teknis dan Performa AUVEST: Rompi Pendingin Otomatis Berbasis Wearable Thermoelectric Cooler untuk Mitigasi Risiko Heat Stress - Wildan, Muchammad Adam; Rayhana, Amelia Avril; Nabila, Nadia Hanifan; Irwanto, Bian Shabri Putri (UI Scholars Hub, 2025)
Heat stress is a serious threat to construction workers that can reduce productivity and even threaten lives. Existing cooling vest innovations still have limitations, such as weight, manual systems, and the risk of leakage. This study aims to analyze the effectiveness of the Automatic Vest (AUVEST), an automatic cooling vest based on Wearable Thermoelectric Cooler and the Internet of Things (IoT), in preventing the risk of heat stress. The method used is experimental with trials on one construction worker in indoor and outdoor environments. AUVEST is equipped with temperature sensors (DS18B20, TMP102) and humidity (DHT11), whose data is processed by an ESP8266 microcontroller to automatically activate the Peltier module based on the Heat Stress Index (HSI) indicator ≥28 and internal temperature ≥35°C. The performance test results show that AUVEST successfully activates the cooling system automatically in outdoor environments, with the temperature reduction rate reaching a peak of 6.91°C in the 7th minute and stabilizing at 6.65°C. AUVEST weighs only 992 grams and has a battery life of 8 hours, outperforming similar products. It was concluded that AUVEST is effective as an innovative, ergonomic, and intelligent solution for heat stress prevention in construction workers. Keywords: Heat Stress, Construction, Automatic Cooling Vest, Wearable Thermoelectric Cooler